The impact of recycled coarse aggregates obtained from waste concretes on lightweight pervious concrete properties - Kaplan, Gokhan; Gulcan, Aslinur; Cagdas, Betul; Bayraktar, Oguzhan Yavuz (Springer Science and Business Media LLC, 2021)
Significant environmental damage can result from the use of natural resources such as cement, aggregate, and water in concrete production. Thus, more sustainable alternatives for concrete production are needed to protect the environment and natural resources. In this study, lightweight pervious concrete production involving recycled coarse aggregates (RCAs) with potential to cause environmental pollution was investigated. First, RCAs were produced from concretes possessing low compressive strength and were classified. Second, pervious concretes were produced from these RCAs. Third, the mechanical properties, permeability, and abrasion strength of the pervious concretes were determined. The water/cement (w/c) ratios of the mixtures were determined to be 0.32, 0.34, and 0.36, and the aggregate/cement (a/c) ratios were selected to be 3.5 and 4. Twelve different pervious concretes were produced and tested in total. The bulk densities (BD) of the mortars varied over an interval of 1160-1080 kg/m3. The aim was to design pervious concretes with lightweight bulk densities. When the w/c ratio was 0.34, the compressive, splitting tensile and abrasion strengths were high. The compressive strength of the pervious concretes varied over an interval of 1.50-2.00 MPa. It was determined that for optimal permeability, the most appropriate w/c ratio was 0.36, and the best a/c ratio was 4. When the a/c ratio was 4, the strength values were high, and as a result, the mechanical properties were poor. With respect to aggregate gradation, it was determined that a grain size distribution of 9.50-12.50 mm was most suitable for this pervious concrete. Recycled aggregates with low strength produced low strength concrete. Therefore, the pervious concrete produced in this study is most suitable for pedestrian roads where heavy vehicle traffic does not exist.
Keywords: Compressive Strength; Waste Management; Construction Materials; Industrial Waste; Recycling; 11. Sustainability; 12. Responsible consumption